Basic reproduction number and effective reproduction number for North Cyprus for fighting Covid-19 - Evren Hincal; Bilgen Kaymakamzade; Nezihal Gokbulut (Қарағанды университетінің хабаршысы. Математика сериясы, 2020)
The aim of this paper is to show how North Cyprus fought with Covid-19 by using R0 and Rt, as herd immunity. For that purpose, we used a SEIR model for basic reproduction number, R0, and calculated Rt values by using R0 values. North Cyprus is the first country in Europe to free from Covid-19 epidemic. One of the most important reasons for this is that the government decided to tackle Covid-19 pandemic by using R0 and Rt daily. For R0, we constructed a new SEIR model by using real data for North Cyprus. From March 11, 2020 to May 15, 2020, R0 varies from 0.65 to 2.38.